Three Norwegian brothers all European 1500m champions: What is the secret? - Tjelta, L. I. (International Journal of Sports Science & Coaching, 2019)
The aim of this study was to analyse the performance development and training structure of three Norwegian brothers, HI, FI and JI who are all European 1500m champions, and to examine to what extent training, environment and family support has been decisive in their development. Their performance development and training from the age of 13 was examined through analysis of the Norwegian Athletic Federation (Norges Friidrettsforbund) all-time best results for boys in 800m and 1500m; analysis of training diaries; observation of training sessions; and dialogue with the three runners, their father and coach and their mother. All three were very physically active from a young age, and they have taken part in different sports. In the preparation period leading up to the 2018 and 2019 seasons, these three athletes ran an average of 140-160km/week, with 23-25% at and above anaerobic threshold pace. Training intensity was monitored and controlled via blood lactate measurements taken during all interval sessions. Throughout childhood and adolescence, the boys were highly motivated and strongly encouraged to take part in sport and training by their close family. All the three were coached by their father. An active childhood, a gradual progression in training volume, strong family support, mental toughness, a high volume of training at and above anaerobic threshold, and mindful monitoring and regulation of training intensity have brought these brothers to a top international level in distance running.